The evaluation of pace of play in hockey - Silva, R. M.; Davis, J.; Swartz, T. B. (Journal of Sports Analytics, 2018)
This paper explores new definitions for pace of play in ice hockey. Using detailed event data from the 2015-2016 regular season of the National Hockey League (NHL), the distance of puck movement with possession is the proposed criterion in determining the pace of a game. Although intuitive, this notion of pace does not correlate positively and strongly with expected and familiar quantities such as goals scored and shots taken.